Early Pep-13-induced immune responses are SERK3A/B-dependent in potato - Nietzschmann, Linda (Sci Rep, 2019)
Potato plants treated with the pathogen-associated molecular pattern Pep-13 mount salicylic acid- and jasmonic acid-dependent defense responses, leading to enhanced resistance against Phytophthora infestans, the causal agent of late blight disease. Recognition of Pep-13 is assumed to occur by binding to a yet unknown plasma membrane-localized receptor kinase. The potato genes annotated to encode the co-receptor BAK1, StSERK3A and StSERK3B, are activated in response to Pep-13 treatment. Transgenic RNAi-potato plants with reduced expression of both SERK3A and SERK3B were generated. In response to Pep-13 treatment, the formation of reactive oxygen species and MAP kinase activation, observed in wild type plants, is highly reduced in StSERK3A/B-RNAi plants, suggesting that StSERK3A/B are required for perception of Pep-13 in potato. In contrast, defense gene expression is induced by Pep-13 in both control and StSERK3A/B-depleted plants. Altered morphology of StSERK3A/B-RNAi plants correlates with major shifts in metabolism, as determined by untargeted metabolite profiling. Enhanced levels of hydroxycinnamic acid amides, typical phytoalexins of potato, in StSERK3A/B-RNAi plants are accompanied by significantly decreased levels of flavonoids and steroidal glycoalkaloids. Thus, altered metabolism in StSERK3A/B-RNAi plants correlates with the ability of StSERK3A/B-depleted plants to mount defense, despite highly decreased early immune responses.